"I don't say that I'm a who's who": Negotiating Identity through Humility Work. Issue 2 (31st August 2021) - Laybourn, SunAh M.
Abstract : Research identifies how individuals negotiate undesirable assumptions of group membership through imbuing an identity with new meaning, reframing auxiliary characteristics, or introducing new criteria. When these strategies are limited, how do members retain the identity while navigating the negative inferences? To answer this question, this study examines identification and authentication processes among socialites in VIP bottle service nightlife. I identity a new form of identity talk—humility work—whereby individuals proactively avoid inauthentication of their identity, enact symbolic boundaries against other group members, and avoid the negative inferences of the identity by reframing their participation as an extension of their personal authenticity.